2020
DOI: 10.1016/j.biomaterials.2020.119828
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium and vitamin C supplementation attenuates steroid-associated osteonecrosis in a rat model

Abstract: A B S T R A C TMagnesium (Mg)-based biometal attracts clinical applications due to its biodegradability and beneficial biological effects on tissue regeneration, especially in orthopaedics, yet the underlying anabolic mechanisms in relevant clinical disorders are lacking. The present study investigated the effect of magnesium (Mg) and vitamin C (VC) supplementation for preventing steroid-associated osteonecrosis (SAON) in a rat experimental model. In SAON rats, 50 mg/kg Mg, or 100 mg/kg VC, or combination, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(41 citation statements)
references
References 89 publications
2
35
0
Order By: Relevance
“…Niflumic acid, a Cl − channel antagonist, does not alter Mg 2+ currents, indicating that extracellular Cl − has no influence on the transport of Mg 2+ [ 73 ]. Besides, both in vitro and in vivo results demonstrate that the high mineralization is realized with a concentration of 0.8 mM Mg 2+ , which is consistent with previous study [ 37 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Niflumic acid, a Cl − channel antagonist, does not alter Mg 2+ currents, indicating that extracellular Cl − has no influence on the transport of Mg 2+ [ 73 ]. Besides, both in vitro and in vivo results demonstrate that the high mineralization is realized with a concentration of 0.8 mM Mg 2+ , which is consistent with previous study [ 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…After fixation in 4% paraformaldehyde (PFA) for 24 h, bone tissues were decalcified in 10% ethylene diamine tetraacetic acid (EDTA, pH 7.4, Sigma, cat# 798681) for 14 days, embedded in paraffin to prepare sections (5 μm thick) for routine staining [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Zheng LZ et al. [ 27 ] showed a good outcome using steroid-associated osteonecrosis model of rat. Traumatic ONFH was also common in clinical and the model of ONFH has the advantages of being fast and stable, so we ameliorated a rat model of traumatic ONFH to evaluate the efficacy of zoledronic acid treatment.…”
Section: Discussionmentioning
confidence: 99%
“…9 Their results also revealed that vitamin C supplementation led to improved bone mineral density (BMD) and bone volume, a higher number of osteoblasts and osteoclasts, and increased expression of osteoblast differentiation genes in OVX rats. 9 Similarly, Zheng et al 33 Recent human studies have examined the link between vitamin C and fracture risk. [36][37][38] A study by Sun et al 36 evaluated the connection between antioxidant intake and risk of hip fracture in the elderly Chinese.…”
Section: Bone Healing and Osteoporosismentioning
confidence: 99%